Oxidative and Non-Oxidative Antimicrobial Activities of the Granzymes - Lavergne, Marilyne; Hernández-Castañeda, Maria Andrea; Mantel, Pierre-Yves; Martinvalet, Denis; Walch, Michael (Frontiers in Immunology, 2021)
Cell-mediated cytotoxicity is an essential immune defense mechanism to fight against viral, bacterial or parasitic infections. Upon recognition of an infected target cell, killer lymphocytes form an immunological synapse to release the content of their cytotoxic granules. Cytotoxic granules of humans contain two membrane-disrupting proteins, perforin and granulysin, as well as a homologous family of five death-inducing serine proteases, the granzymes. The granzymes, after delivery into infected host cells by the membrane disrupting proteins, may contribute to the clearance of microbial pathogens through different mechanisms. The granzymes can induce host cell apoptosis, which deprives intracellular pathogens of their protective niche, therefore limiting their replication. However, many obligate intracellular pathogens have evolved mechanisms to inhibit programed cells death. To overcome these limitations, the granzymes can exert non-cytolytic antimicrobial activities by directly degrading microbial substrates or hijacked host proteins crucial for the replication or survival of the pathogens. The granzymes may also attack factors that mediate microbial virulence, therefore directly affecting their pathogenicity. Many mechanisms applied by the granzymes to eliminate infected cells and microbial pathogens rely on the induction of reactive oxygen species. These reactive oxygen species may be directly cytotoxic or enhance death programs triggered by the granzymes. Here, in the light of the latest advances, we review the antimicrobial activities of the granzymes in regards to their cytolytic and non-cytolytic activities to inhibit pathogen replication and invasion. We also discuss how reactive oxygen species contribute to the various antimicrobial mechanisms exerted by the granzymes.